Airway Basal Cells Mediate Hypoxia-Induced EMT by Increasing Ribosome Biogenesis - Hou, Yapeng; Ding, Yan; Du, Danni; Yu, Tong; Zhou, Wei; Cui, Yong; Nie, Hongguang (Frontiers in Pharmacology, 2021)
Excessive secretion of airway mucus and fluid accumulation are the common features of many respiratory diseases, which, in turn, induce cell hypoxia in the airway epithelium, resulting in epithelial–mesenchymal transition (EMT) and ultimately fibrosis. However, the mechanisms of EMT induced by hypoxia in the airway are currently unclear. To mimic the status of edematous fluid retention in the airway, we cultured primary mouse tracheal epithelial cells (MTECs) in a liquid–liquid interface (LLI) mode after full differentiation in a classic air–liquid interface (ALI) culture system. The cell hypoxia was verified by the physical characteristics and lactate production in cultured medium as well as HIF expression in MTECs cultured by LLI mode. EMT was evidenced and mainly mediated by basal cells, supported by flow cytometry and immunofluorescence assay. The differently expressed genes of basal and other airway epithelial cells were found to be enriched in the ribosome by our analysis of an MTEC single-cell RNA sequencing data set and Myc, the global regulator of ribosome biogenesis was identified to be highly expressed in basal cells. We next separated basal cells from bulk MTECs by flow cytometry, and the real-time PCR results showed that ribosome biogenesis was significantly upregulated in basal cells, whereas the inhibition of ribosome biogenesis alleviated the phosphorylation of the mammalian target of rapamycin/AKT and abrogated hypoxia-induced EMT in MTECs. Collectively, these observations strongly suggest that basal cells in the airway epithelium may mediate the process of hypoxia-induced EMT, partly through enhancing ribosome biogenesis.